2018
DOI: 10.1021/acs.bioconjchem.7b00823
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Water and Polymer Species and Rheological Properties of Supramolecular Polypseudorotaxane Gels Suitable for Bone Regeneration

Abstract: The aim of this work was to prepare polypseudorotaxane-based supramolecular gels combining αCD with two temperature-responsive copolymers of different architecture (i.e., linear poloxamer P and X-shaped poloxamine T), at the lowest concentration as possible to form syringeable depots, and to shed light on the self-diffusion and spatial closeness of all components (including water) which in turn may determine the cooperative self-assembly phenomena and the performance of the gels at the macroscopic level. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
7
2
Order By: Relevance
“…The visualization of two phases in the PF127/αCD 7% system suggested that the polypseudorotaxanes were somehow collapsed and could not form a complete 3D supramolecular gel filling the whole volume of the dispersion. This phase separation was not observed in previous reports on PF127/αCD polypseudorotaxanes prepared in pure water [37][38][39][40] and may be caused by an enhanced aggregation of the αCDs in the buffer pH 4.9 used to prepare the formulations. This acid pH adversely affects the solubility of the αCDs but is preferable for topical skin formulations.…”
Section: Polypseudorotaxanes Formation and Characterization In Solid contrasting
confidence: 74%
See 2 more Smart Citations
“…The visualization of two phases in the PF127/αCD 7% system suggested that the polypseudorotaxanes were somehow collapsed and could not form a complete 3D supramolecular gel filling the whole volume of the dispersion. This phase separation was not observed in previous reports on PF127/αCD polypseudorotaxanes prepared in pure water [37][38][39][40] and may be caused by an enhanced aggregation of the αCDs in the buffer pH 4.9 used to prepare the formulations. This acid pH adversely affects the solubility of the αCDs but is preferable for topical skin formulations.…”
Section: Polypseudorotaxanes Formation and Characterization In Solid contrasting
confidence: 74%
“…Dt offers information about the molecular organization as it depends on the molecule size that can be calculated from the Stokes-Einstein equation. This value was slightly higher than that previously reported for related block copolymers [40]. In the presence of both cyclodextrins, the chemical environment surrounding these groups changed, confirming that the inclusion phenomenon took place.…”
Section: Nmr Studiescontrasting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, the presence of natamycin only caused a minor decrease in both G′ and G″, which means that Pluronic P103 attenuated the effects of hosting natamycin in Soluplus cores probably because of a preferential interaction of αCD molecules with the PEO blocks of Pluronic P103. It has been previously observed by means of nuclear magnetic resonance diffusion studies that the threading of αCD along PEO moieties of Pluronic F127 causes a remarkable decrease in αCD mobility [43], which is typical of strong complex formation. The decrease in the mobility of αCDs due to the formation of a transient complex with Soluplus was less marked [35], which supports our hypothesis of a preferential threading of αCDs along Pluronic P103 in the mixed micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the addition of cyclodextrins, a cyclic oligosaccharide composed of six to eight glucopyranose units, can lead to the formation of inclusion complexes with certain polymer regions. The toxicity of these compounds decreases with increasing number of glucopyranose units, thus, gamma cyclodextrins are less toxic than alpha or beta ones [11]. Synthetic polymers, like poly( dl -lactide-co-glycolide) (PLGA), poly( dl -lactide) (PLA), poly(vinyl alcohol) (PVA), poly(acrylic acid) (PAA), polyethylene glycol (PEG), can enhance and control the mechanical strength and degradation rates of hydrogels.…”
Section: Introductionmentioning
confidence: 99%